PENGARUH PEDAL EXERCISE DAN PEREGANGAN OTOT BETIS LEBIH EFEKTIF DALAM MENINGKATKAN NILAI AMBANG NYERI OTOT BETIS PADA PEMOTONG KAIN DI KECAMATAN KEDIRI KABUPATEN TABANAN - Ni Putu Ayu Sasmita Sari; I Made Niko Winaya; I Putu Adiartha Griadhi; I Putu Gede Adiatmika (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2018)
ABSTRACT Stands work attitude in a long time cause muscle complaints on fabric cutters worker. The purpose of this studyis knowing whether effect of pedal exercise and stretching calf muscles more effective to increase threshold of calfmuscle pain on the fabric cutters worker. Measurement of the value of pain was measured using a sphygmomanometerThis study is experimental research using Pre Test and Post Test Control Group Design. These samples included 20people who were divided into group treatment and group control. Group treatment was given pedal exercise andstretching calf muscles, while Group control without treatment. Hypothesis test by paired sample t-test in group treatmentis p=0.000 with a mean difference 30.00±16.99, that mean is it can increase threshold of calf muscle pain, while incontrol group is p=0.758 with a mean difference 1.00±9.94, that mean is it can’t increase threshold of calf muscle pain.At different test between treatment group and control group using independent sample t-test was obtained p=0.000(p<0.05). Based on these results, it can be concluded that pedal exercise and stretching calf muscles more effective toincrease threshold of calf muscle pain. Keywords: pedal exercise, stretching, calf muscle pain, fabric cutter